Social Media Problematic Use and Depression: A Quantitative Study of Pakistani Adults (Journal of Asian Development Studies, 2025)
Social media platforms offer opportunities for sharing content and interacting online. However, excessive use, especially among young adults, can lead to mental health challenges. This study's objective is to find an association between social media use and depression among young adults in Pakistan. Using purposive sampling, 144 participants aged 18 to 25 (110 men, 34 women) who had been active on social media for at least one year were included. Problematic social media use was measured using the Bergen Social Media Addiction Scale (Andreassen et al., 2016), and depression was assessed with the Beck Depression Inventory (Beck, 1961). The findings revealed a significant positive correlation between social media problematic use and depression. Additionally, regression analysis showed that social media use is a significant predictor of depression. The study highlights the importance of addressing excessive social media use to improve mental well-being, contextualizes the results within existing research, and provides recommendations while noting the study's limitations.